The Effect of The Cucumber Consumption To The Level of Sodium Potassium in Mus Muscullus's Urine Production - Elicia, Vincensa; Tjipto, Bambang Wasito; Novita, Bernadette Dian (Folia Medica Indonesiana, 2021)
Cucumber (Cucumis sativus L.). was known for lowering blood pressure agents. Some researches show that Cucumber had a similar mechanism with a loop diuretic (Furosemide), exceeding sodium and potassium excretion. However, a part of Cucumber that gives a better effect on managing water and sodium balance remains unknown. This study was to explain the differences potential diuretic among parts of Cucumber (Cucumis sativus L.). This study was using a post-test only control group designed in animals. There were 44 male Mus musculus tested in this study. All of the animal testings was divided into 9 different treatment groups and 2 control groups. All Mus musculus got 1 mL methanol extract of Cucumber (Cucumis sativus L.) according to their group. The animal testing was put on metabolic cage to measure urine volume for 24 hours. The flesh and rind part of Cucumber (Cucumis sativus L.) showed a similar result with furosemide as diuretics agents. However, whole part of the fruit of Cucumber (Cucumis sativus L.) (flesh, rind, and seed) showed as natriuretic dan kaliuretic, Cucumber (Cucumis sativus L.) has a similar potential diuretic with Furosemide. Even in low concentrations of Cucumber extract, it led to having a potential diuretic, with natriuretic and kaliuretic effects in the whole part of the fruit. This could be suggested to people with chronic kidney diseases to prevent hyperkalemia.